Variation in outcome of hospitalised patients with out-of-hospital cardiac arrest from acute coronary syndrome: a cohort study - Keith Couper (Health Services and Delivery Research, 2018)
Background: Each year, approximately 30,000 people have an out-of-hospital cardiac arrest (OHCA) that is treated by UK ambulance services. Across all cases of OHCA, survival to hospital discharge is less than 10%. Acute coronary syndrome (ACS) is a common cause of OHCA. Objectives: To explore factors that influence survival in patients who initially survive an OHCA attributable to ACS. Data source: Data collected by the Myocardial Ischaemia National Audit Project (MINAP) between 2003 and 2015. Participants: Adult patients who had a first OHCA attributable to ACS and who were successfully resuscitated and admitted to hospital. Main outcome measures: Hospital mortality, neurological outcome at hospital discharge, and time to all-cause mortality. Methods: We undertook a cohort study using data from the MINAP registry. MINAP is a national audit that collects data on patients admitted to English, Welsh and Northern Irish hospitals with myocardial ischaemia. From the data set, we identified patients who had an OHCA. We used imputation to address data missingness across the data set. We analysed data using multilevel logistic regression to identify modifiable and non-modifiable factors that affect outcome. Results: Between 2003 and 2015, 1,127,140 patient cases were included in the MINAP data set. Of these, 17,604 OHCA cases met the study inclusion criteria. Overall hospital survival was 71.3%. Across hospitals with at least 60 cases, hospital survival ranged from 34% to 89% (median 71.4%, interquartile range 60.7–76.9%). Modelling, which adjusted for patient and treatment characteristics, could account for only 36.1% of this variability. For the primary outcome, the key modifiable factors associated with reduced mortality were reperfusion treatment [primary percutaneous coronary intervention (pPCI) or thrombolysis] and admission under a cardiologist. Admission to a high-volume cardiac arrest hospital did not influence survival. Sensitivity analyses showed that reperfusion was associated with reduced mortality among patients with a ST elevation myocardial infarction (STEMI), but there was no evidence of a reduction in mortality in patients who did not present with a STEMI. Limitations: This was an observational study, such that unmeasured confounders may have influenced study findings. Differences in case identification processes at hospitals may contribute to an ascertainment bias. Conclusions: In OHCA patients who have had a cardiac arrest attributable to ACS, there is evidence of variability in survival between hospitals, which cannot be fully explained by variables captured in the MINAP data set. Our findings provide some support for the current practice of transferring resuscitated patients with a STEMI to a hospital that can deliver pPCI. In contrast, it may be reasonable to transfer patients without a STEMI to the nearest appropriate hospital. Future work: There is a need for clinical trials to examine the clinical effectiveness and cost-effectiveness of invasive reperfusion strategies in resuscitated OHCA patients of cardiac cause who have not had a STEMI. Funding: The National Institute for Health Research Health Services and Delivery Research programme.